L’atracció pel món clàssic de Bizanci a Grècia i Troia (ss. XIII-XV) - Escartí, Vicent Josep, 1964- (Studia Iberica et Americana: journal of Iberian and Latin American literary and cultural studies, 2014)
This article throws a glimpse to the presence of Greek references —and also Trojans—, in the historiography and Catalan medieval literature. Not as for the authors of the antiquity, especially philosophers, who had not disappear completely and who will increase their presence with the humanism, as to the geographical and cultural abstract, fi rst, and then, more concrete, when some episodes of classic history will be spread through certain texts. In particular, the mythology and the Greek past will be in circulation from Històries troianes of Guido delle Colonne and Italian humanism. In any case, it will pass from some vague references to a fashion which was destined to succeed during the second half of the 15th and to that so many authors will be added.